Alien introgressions and chromosomal rearrangements do not affect the activity of gliadin-coding genes in hybrid lines of Triticum aestivum L. × Aegilops columnaris Zhuk - A. Yu. Novoselskaya-Dragovich; A. A. Yankovskaya; E. D. Badaeva (Вавиловский журнал генетики и селекции)
Using chromosome C-banding and electrophoresis of grain storage proteins, gliadins, 17 Triticum aestivumAegilops columnaris lines with substitutions of chromosomes of homoeologous groups 1 and 6 were examined. Based on their high polymorphism, gliadins were used to identify alien genetic material. For all of the lines examined, electrophoretic analysis of gliadin spectra confirmed substitution of wheat chromosomes 6A, 6D or 1D for the homoeologous Aegilops chromosomes of genomes Uс or Xс. The substitution manifested in the disappearance of the products of gliadin-coding genes on chromosomes 6A, 6D or 1D with the simultaneous appearance of the products of genes localized on alien chromosomes of genomes Uс or Xс. Thus, Aegilops chromosomes were shown to be functionally active in the alien wheat genome. The absence of alien genes expression in the lines carrying a long arm deletion in chromosome 6Xc suggested that the gliadin-coding locus moved from the short chromosome arm (its characteristic position in all known wheat species) to the long one. This is probably associated with a large species-specific pericentric inversion. In spite of losing a part of its long arm and combination with a non-homologous chromosome of a different genome (4BL), chromosome 1D was fully functioning. For Aegilops, the block type of gliadin components inheritance was shown, indicating similarity in the structural organization of gliadin-coding loci in these genera. Based on determining genetic control of various polypeptides in the electrophoretic aegilops spectrum, markers to identify Ae. columnaris chromosomes 1Xс, 6Xс and 6Uс were constructed.